The Influence of Authentic Leadership on Public Employees Analyzed through Self- Determination Theory: A Case Study in Republic of Moldova - Bordei, Irina; Vieira dos Santos, Joana; Gonçalves, Gabriela; Sousa, Cátia (Journal of Tourism, Sustainability and Well-being, 2019)
This study examines the influence of authentic leadership on employees from public organizations analyzed through self-determination theory. Over the years, researchers analyzed different particularities of authentic leadership and its importance in nowadays’ society. However, fewer researchers were interested in analyzing the influence of authentic leadership on employees through self-determination theory, especially in the perception of public ethical behavior. The theoretical model of this study proposes that authentic leadership is negatively correlated with public employees’ positive attitude toward unethical behavior, namely corrupt acts. Also, authentic leadership and job satisfaction are positively related with public employees’ work motivation. This positive relationship contributes to the decrease level of public employees’ positive attitude toward corruption acts. The study was realized in different public organizations from Republic of Moldova. The total sample is composed by 98 participants. The hypotheses were tested through Multiple Hierarchical Regression. The study results showed that authentic leadership has a positive impact on work motivation. However, job satisfaction does not have any influence on public employees’ perception of corruption acts. By contrast, authentic leadership behavior does have a positive impact on public employees’ perception of corruption acts, but only when they perceive these acts as less serious.